Evaluating Nigerian Government Policies on Poverty Alleviation and Food Security in the Conflict-Affected North-East Region - Abdulazeez , Sajoh; Hamidu, Auwal (Unisia, 2024)
This study examines the effectiveness of Nigerian government policies in combating poverty and food insecurity in the North-East, with a focus on the BAY states, Borno, Adamawa, and Yobe. Despite abundant natural resources and successive poverty alleviation programs, these regions continue to experience severe deprivation due to protracted insurgency, economic instability, and governance failures. Using a qualitative research design based on secondary data from policy documents, institutional reports, and international organizations, the study analyzes how macroeconomic reforms, such as fuel subsidy removal and currency devaluation, intersect with local agricultural and social protection policies. The findings reveal that while national and state frameworks—including the National Agricultural Technology and Innovation Policy and state-level Food Security Sector Strategies—provide structured approaches to recovery, weak institutional coordination, inflation, and insecurity undermine their effectiveness. Comparative evidence from Sub-Saharan Africa suggests that decentralized interventions and public–private partnerships enhance resilience only when supported by accountable governance and sustainable financing. The discussion integrates the Rational Comprehensive Model of Decision-Making to interpret the trade-offs between economic rationality and social welfare, emphasizing the need for adaptive, participatory policy frameworks. Overall, the study concludes that addressing food insecurity and poverty in Nigeria requires aligning macroeconomic reforms with inclusive social protection and institutional reform. It contributes to the academic discourse by linking rational policymaking, governance quality, and humanitarian resilience, offering evidence-based recommendations for achieving sustainable food security and poverty eradication in fragile contexts.